Component Based Software Development (SDLC). - Krishna, M. V. L. Phani; Reddy, G. Sasank; Madhav, M. Venu; Kumar, J. Pavan; K., Amarendra (Turkish Journal of Physiotherapy Rehabilitation, 2021)
Element Primarily Based Computer Code Engineering (Cbse) Has Provided Price Effective, Quick and Standard Approach for Developing Complex Software. Cbse Is Especially Supported the Idea of Reusability, Except These Cbse Has Many Blessings Similarly as Challenges That Are Summarized During This Paper. Software Development Needs to Use Reusable Parts and May Be Selected from Component Repository and Assembled to Get an Application. Development of Components and Their Assembly Is Totally Different from Ancient Software Which Results in The Necessity of Latest Development Paradigms for Element Primarily Based Systems (Cbs). Sdlc Provides Planned and Systematic Arrangement of Activities to Be Disbursed to Deliver Prime Quality Merchandise Among Expenses.